Method for brazing quartz fiber reinforced silicon dioxide composite material and Invar alloy with assistance of aluminothermic reduction surface modification

Through aluminum thermal reduction surface modification and the use of AgCuTi/Nb/AgCu composite intermediate layer, the problem of low interface bonding strength in brazing of SiO2f/SiO2 composite materials and Invar alloys is solved, and the strength and stability of the brazing connection are significantly improved. .

CN119187744AActive Publication Date: 2024-12-27HARBIN INST OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411370425.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-27
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

The wetting performance of SiO2f/SiO2 composite material has poor wetting performance, which makes it difficult to carry out the interface metallurgy reaction. The reaction of Fe and Ni elements in Invar alloy with Ti elements in AgCuTi brazing weakens the interface bonding strength, affecting the brazing joint Mechanical properties.

Method used

Using aluminum thermal reduction surface modification assisted with brazing of SiO2f/SiO2 composite material and Invar alloy, Al deposition layer was deposited on the surface of SiO2f/SiO2 composite material and aluminum thermal reduction modification was carried out to generate Al oxide to promote the moisturization of AgCuTi brazing. Wetness is used to block the reaction between Ti elements and Fe and Ni elements in Invar alloy by using AgCuTi/Nb/AgCu composite intermediate layer to optimize the weld structure.

Benefits of technology

The wetting properties of the surface of SiO2f/SiO2 composite materials are improved, the joint strength and stability of brazed connections are improved, and the reliability of the welded joints is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119187744A_ABST
    Figure CN119187744A_ABST
Patent Text Reader

Abstract

The invention discloses a method for brazing a quartz fiber reinforced silicon dioxide composite material and an Invar alloy under the assistance of aluminothermic reduction surface modification, and relates to a method for brazing a SiO2f / SiO2 composite material and the Invar alloy. In order to solve the problems that the wettability of active brazing filler metal on the surface of the SiO2f / SiO2 composite material is poor and the interface bonding strength is low, SiO2 on the surface of the SiO2f / SiO2 composite material is reduced into Si, an oxide of Al is generated, and after brazing, AgCuTi brazing filler metal reacts with the oxide of Al to generate a Ti3Al phase to promote spreading and wetting of the AgCuTi brazing filler metal on the surface of the SiO2f / SiO2 composite material, so that the wettability is improved; an AgCuTi / Nb / AgCu composite middle layer is adopted to assist brazing of a SiO2f / SiO2 composite material and an Invar alloy, and Nb is used for preventing a Ti element from reacting with Fe and Ni elements in the Invar alloy to generate a brittle intermetallic compound, so that the organization structure of a welding seam is optimized, the strength of a brazing connection joint is improved, and the stability and reliability of the welding joint are further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a SiO 2f Method for brazing of / SiO2 composite material and Invar alloy. Background Art

[0002] With the rapid development of science and technology, the performance requirements of devices and components in the fields of aerospace, electronics and microelectronics, biomedicine, etc. have been upgraded, and the requirements for materials are strict. The importance of material research has become prominent in many fields, especially in key areas, which require materials to have multiple high-performance characteristics. It is urgent to improve the comprehensive performance of materials, and composite materials have emerged. Composite materials combine multiple advantages and have excellent performance. SiO 2f / SiO2 composite material is a new type of composite material, which not only has the high hardness and high melting point of ceramic materials, but also has good wave transmission and thermal shock resistance. 2f / SiO2 composite materials have significant advantages such as light weight and high temperature resistance. 2f / SiO2 composite materials have been widely used in high temperature fields. 2f The low density and light weight of SiO2 composite materials greatly reduce the weight of components. 2f The mechanical processing performance of SiO2 composite materials is poor. For components with complex structures, direct processing is difficult, so it is necessary to connect them with other materials. 2f The brazing connection of / SiO2 composite materials and Invar alloy can produce composite components with complex structures, which not only greatly reduces the weight of the components but also increases their operating temperature.

[0003] Brazing method to connect SiO 2f There are two major difficulties in the soldering of / SiO2 composite materials and Invar alloys: First, due to the active solder in SiO 2f The poor wettability of the surface of the Invar / SiO2 composite material makes it difficult for the metallurgical reaction on the interface to proceed, which further leads to a significant decrease in the mechanical properties of the brazed joint. Second, since the Fe and Ni elements in the Invar alloy easily react with the Ti element in the AgCuTi brazing filler metal, this interaction weakens the bonding between the AgCuTi brazing filler metal and the SiO2 2f / SiO2 composite material interface reaction activity, affecting the interface bonding strength. Summary of the invention

[0004] The present invention aims to solve the problem of active solder in SiO 2f In order to solve the problems of poor wettability and low interface bonding strength of SiO2 composite materials, a surface modification method assisted by aluminothermic reduction was proposed. 2f / SiO2 composite material and Invar alloy brazing method,

[0005] The present invention is aluminothermic reduction surface modification auxiliary SiO 2f The method for brazing the / SiO2 composite material with Invar alloy is carried out according to the following steps:

[0006] 1. SiO 2f Pre-welding treatment of SiO2 composite materials:

[0007] ①、 SiO 2f / SiO2 composite material is cut to a predetermined size;

[0008] ②, cut SiO 2f / SiO2 composite materials are ultrasonically cleaned;

[0009] ③. After ultrasonic cleaning, SiO 2f / SiO2 composite material is calcined;

[0010] The calcination process is as follows: heating to 700°C-800°C at a heating rate of 5-10°C / min, keeping the temperature for 60-120min, and cooling to ≤150°C at a cooling rate of ≤5°C / min;

[0011] ④. Polishing SiO 2f / SiO2 composite material surface to be welded;

[0012] ⑤、The polished SiO 2f / SiO2 composite materials are ultrasonically cleaned;

[0013] ⑥In SiO 2f Depositing an Al deposition layer on the surface to be welded of the / SiO2 composite material;

[0014] The deposition process of the Al deposition layer is as follows: SiO 2f The / SiO2 composite material is clamped on the workbench of the magnetron sputtering device, and the target and SiO 2f / SiO2 composite material, and evacuate the magnetron sputtering device to a vacuum of ≤5×10 -3 Pa, then introduce 80-150sccm of argon at a constant rate, keep the working gas pressure at 0.1-0.8Pa, and set the frequency of the pulse power supply to f r =500-700Hz, the discharge pulse width is set to t ON = 200-400μs, select the constant current mode, set the average discharge current to 0.3-0.5A, and then gradually increase the voltage applied to the target until the target is completely melted; then sputter and deposit on SiO 2f An Al deposition layer is obtained on the surface to be welded of the / SiO2 composite material; the target material is an aluminum target;

[0015] 7. SiO 2f / SiO2 composite material surface aluminothermic reduction modification;

[0016] The SiO2 with Al deposition layer on the surface to be welded 2f The / SiO2 composite material is placed in a vacuum furnace, first heated to 650°C-700°C at a heating rate of 5-10°C / min and kept at this temperature for 1-4h for reduction modification, and then cooled to ≤150°C at a cooling rate of ≤5°C / min;

[0017] 2. Pre-welding treatment of Invar alloy:

[0018] The Invar alloy is cut to a predetermined size, the surface to be welded of the Invar alloy is polished, and then ultrasonically cleaned;

[0019] 3. Pre-welding treatment of composite intermediate layer:

[0020] Taking AgCuTi foil, AgCu foil and Nb foil, and cutting them into predetermined sizes, and then grinding, leveling and ultrasonic cleaning them in sequence after cutting;

[0021] 4. Assembly of test pieces to be welded:

[0022] The SiO obtained in step 1 2f / SiO2 composite material, Invar alloy obtained in step 2, AgCuTi foil, AgCu foil and Nb foil obtained in step 2 are stacked to obtain a welded specimen; the stacking order is SiO 2f / SiO2 composite materials, AgCuTi foil, Nb foil, AgCu foil, Invar alloy, SiO 2f The surface to be welded of the / SiO2 composite material faces the AgCuTi foil, and the surface to be welded of the Invar alloy faces the AgCu foil;

[0023] 5. Vacuum brazing connection: Place the assembled test piece into a vacuum brazing furnace with a vacuum degree of 5×10 -3 Pa, heat to 840-900℃ at a heating rate of 5-10℃ / min, keep warm for 10-40min, and then cool to ≤150℃ at a cooling rate of ≤5℃ / min.

[0024] The principles and beneficial effects of the present invention are:

[0025] The present invention is based on SiO 2f / SiO2 composite material surface aluminothermic reduction modification, SiO 2fThe SiO2 on the surface of the AgCuTi / SiO2 composite material is reduced to Si and generates Al oxide. After brazing, the AgCuTi solder reacts with Al oxide to generate Ti3Al phase, which promotes the AgCuTi solder to form a Ti3Al phase. 2f / SiO2 composite material surface spreading and wetting, thereby improving the AgCuTi solder on the SiO 2f / SiO2 composite surface wettability; In addition, AgCuTi / Nb / AgCu composite intermediate layer was used to assist brazing SiO 2f / SiO2 composite materials and Invar alloys use Nb to block the reaction of Ti elements with Fe and Ni elements in Invar alloys to form brittle intermetallic compounds, thereby optimizing the organizational structure of the weld, improving the strength of the brazed connection, and further improving the stability and reliability of the welded joint. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The SiO obtained in Example 1 2f Interface microstructure of the brazed joint between / SiO2 composite material and Invar alloy;

[0027] Figure 2 The SiO obtained in Example 2 2f Interface microstructure picture of brazed joint between / SiO2 composite material and Invar alloy. DETAILED DESCRIPTION

[0028] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any reasonable combination of the specific implementation modes.

[0029] Specific implementation method 1: In this implementation method, the surface modification of SiO is assisted by aluminothermic reduction. 2f The method for brazing the / SiO2 composite material with Invar alloy is carried out according to the following steps:

[0030] 1. SiO 2f Pre-welding treatment of SiO2 composite materials:

[0031] ①、 SiO 2f / SiO2 composite material is cut to a predetermined size;

[0032] ②, cut SiO 2f / SiO2 composite materials are ultrasonically cleaned;

[0033] ③. After ultrasonic cleaning, SiO 2f / SiO2 composite material is calcined;

[0034] The calcination process is as follows: heating to 700°C-800°C at a heating rate of 5-10°C / min, keeping the temperature for 60-120min, and cooling to ≤150°C at a cooling rate of ≤5°C / min;

[0035] ④. Polishing SiO 2f / SiO2 composite material surface to be welded;

[0036] ⑤、The polished SiO 2f / SiO2 composite materials are ultrasonically cleaned;

[0037] ⑥In SiO 2f Depositing an Al deposition layer on the surface to be welded of the / SiO2 composite material;

[0038] The deposition process of the Al deposition layer is as follows: SiO 2f The / SiO2 composite material is clamped on the workbench of the magnetron sputtering device, and the target and SiO 2f / SiO2 composite material, and evacuate the magnetron sputtering device to a vacuum of ≤5×10 -3 Pa, then introduce 80-150sccm of argon at a constant rate, keep the working gas pressure at 0.1-0.8Pa, and set the frequency of the pulse power supply to f r =500-700Hz, the discharge pulse width is set to t ON = 200-400μs, select the constant current mode, set the average discharge current to 0.3-0.5A, and then gradually increase the voltage applied to the target until the target is completely melted; then sputter and deposit on SiO 2f An Al deposition layer is obtained on the surface to be welded of the / SiO2 composite material; the target material is an aluminum target;

[0039] 7. SiO 2f / SiO2 composite material surface aluminothermic reduction modification;

[0040] The SiO2 with Al deposition layer on the surface to be welded 2f The / SiO2 composite material is placed in a vacuum furnace, first heated to 650°C-700°C at a heating rate of 5-10°C / min and kept at this temperature for 1-4h for reduction modification, and then cooled to ≤150°C at a cooling rate of ≤5°C / min;

[0041] 2. Pre-welding treatment of Invar alloy:

[0042] The Invar alloy is cut to a predetermined size, the surface to be welded of the Invar alloy is polished, and then ultrasonically cleaned;

[0043] 3. Pre-welding treatment of composite intermediate layer:

[0044] Taking AgCuTi foil, AgCu foil and Nb foil, and cutting them into predetermined sizes, and then grinding, leveling and ultrasonic cleaning them in sequence after cutting;

[0045] 4. Assembly of test pieces to be welded:

[0046] The SiO obtained in step 1 2f / SiO2 composite material, Invar alloy obtained in step 2, AgCuTi foil, AgCu foil and Nb foil obtained in step 2 are stacked to obtain a welded specimen; the stacking order is SiO 2f / SiO2 composite materials, AgCuTi foil, Nb foil, AgCu foil, Invar alloy, SiO 2f The surface to be welded of the / SiO2 composite material faces the AgCuTi foil, and the surface to be welded of the Invar alloy faces the AgCu foil;

[0047] 5. Vacuum brazing connection: Place the assembled test piece into a vacuum brazing furnace with a vacuum degree of 5×10 -3 Pa, heat to 840-900℃ at a heating rate of 5-10℃ / min, keep warm for 10-40min, and then cool to ≤150℃ at a cooling rate of ≤5℃ / min.

[0048] This embodiment has the following beneficial effects:

[0049] This embodiment is based on SiO 2f / SiO2 composite material surface aluminothermic reduction modification, SiO 2f The SiO2 on the surface of the AgCuTi / SiO2 composite material is reduced to Si and generates Al oxide. After brazing, the AgCuTi solder reacts with Al oxide to generate Ti3Al phase, which promotes the AgCuTi solder to form a Ti3Al phase. 2f / SiO2 composite material surface spreading and wetting, thereby improving the AgCuTi solder on the SiO 2f / SiO2 composite surface wettability; In addition, AgCuTi / Nb / AgCu composite intermediate layer was used to assist brazing SiO 2f / SiO2 composite materials and Invar alloys use Nb to block the reaction of Ti elements with Fe and Ni elements in Invar alloys to form brittle intermetallic compounds, thereby optimizing the organizational structure of the weld, improving the strength of the brazed connection, and further improving the stability and reliability of the welded joint.

[0050] Specific implementation method 2: The difference between this implementation method and specific implementation method 1 is that: the ultrasonic cleaning process in step 1② is: using anhydrous ethanol or acetone as a cleaning agent, the ultrasonic cleaning frequency is 70-150kHz, and the ultrasonic cleaning time is 5-60min.

[0051] Specific implementation method three: This implementation method is different from specific implementation method one or two in that: step 1④ SiO 2f The surface to be welded of the SiO2 composite material is polished with 1000-3000 mesh sandpaper to remove surface impurities and ensure that the surface to be welded is smooth and flat.

[0052] Specific implementation method four: This implementation method is different from any one of specific implementation methods one to three in that: the ultrasonic cleaning process in step 1⑤ is: using anhydrous ethanol or acetone as a cleaning agent, an ultrasonic cleaning frequency of 70-150kHz, an ultrasonic cleaning time of 5-60min, and repeating the cleaning 2-3 times.

[0053] Specific embodiment 5: This embodiment is different from any one of specific embodiments 1 to 4 in that: the ultrasonic cleaning process in step 2 is: using anhydrous ethanol or acetone as a cleaning agent, an ultrasonic cleaning frequency of 70-150kHz, an ultrasonic cleaning time of 5-60min, and grinding the surface to be welded of the Invar alloy with 400-1000 mesh sandpaper.

[0054] Specific implementation method 6: This implementation method is different from any one of specific implementation methods 1 to 5 in that: in the polishing process described in step 3, 1000-2000 mesh sandpaper is used to polish the AgCuTi foil and the AgCu foil, and 400-1000 mesh sandpaper is used to polish the Nb foil.

[0055] Specific embodiment 7: This embodiment differs from any one of specific embodiments 1 to 6 in that: in step 3, the AgCuTi foil, AgCu foil and Nb foil are cut to an edge larger than SiO 2f / SiO2 composite material edge of the surface to be welded is 1-2mm.

[0056] Specific implementation eight: This implementation differs from any one of specific implementations one to seven in that: in the flattening process described in step three, a flat plate is used to clamp the AgCuTi foil, the AgCu foil and the Nb foil, and a pressure of 5-10 MPa is applied.

[0057] Specific embodiment nine: This embodiment differs from any one of specific embodiments one to eight in that: the ultrasonic cleaning process described in step three is: using anhydrous ethanol or acetone as a cleaning agent, an ultrasonic cleaning frequency of 70-150kHz, an ultrasonic cleaning time of 5-60min, and repeating the cleaning 2-3 times.

[0058] Specific embodiment 10: This embodiment differs from any one of specific embodiments 1 to 9 in that: the deposition process of the Al deposition layer in step 1⑥ is: SiO 2f The / SiO2 composite material is clamped on the workbench of the magnetron sputtering device, and the target and SiO 2fThe spacing between the / SiO2 composite materials was 10 cm, and the magnetron sputtering device was evacuated to 5×10 -3 Pa, then introduce 100 sccm of argon at a constant rate, keep the working gas pressure at 0.5 Pa, and set the frequency of the pulse power supply to f r =600Hz, the discharge pulse width is set to t ON = 300μs, select the constant current mode, set the average discharge current to 0.4A, and then gradually increase the voltage applied to the target until the target is completely melted; then perform sputtering deposition for 60min. 2f A 6μm Al deposition layer was obtained on the surface to be welded of the / SiO2 composite material.

[0059] Embodiment 1:

[0060] In this embodiment, the surface modification of SiO 2f The method for brazing the / SiO2 composite material with Invar alloy is carried out according to the following steps:

[0061] 1. SiO 2f Pre-welding treatment of SiO2 composite materials:

[0062] ①、 SiO 2f / SiO2 composite material is cut into 4mm×4mm×4mm;

[0063] ②, cut SiO 2f / SiO2 composite materials are ultrasonically cleaned;

[0064] The ultrasonic cleaning process in step 1② is as follows: the cleaning agent is anhydrous ethanol, the ultrasonic cleaning frequency is 100kHz, and the ultrasonic cleaning time is 10min;

[0065] ③. After ultrasonic cleaning, SiO 2f / SiO2 composite material is calcined;

[0066] The calcination process is as follows: heating to 700°C at a heating rate of 10°C / min, keeping the temperature for 60 minutes, and cooling to 100°C at a cooling rate of 5°C / min; calcination can remove SiO 2f / SiO2 composite material internal colloid;

[0067] ④. Polishing SiO 2f / SiO2 composite material surface to be welded;

[0068] Step 1④ SiO 2f The surface to be welded of the SiO2 composite material is polished with 1500-grit sandpaper to remove surface impurities and ensure that the surface to be welded is smooth and flat;

[0069] ⑤、The polished SiO 2f / SiO2 composite materials are ultrasonically cleaned;

[0070] Step 1⑤ The ultrasonic cleaning process is: using anhydrous ethanol as the cleaning agent, the ultrasonic cleaning frequency is 100kHz, the ultrasonic cleaning time is 10min, and the cleaning is repeated 3 times;

[0071] ⑥In SiO 2f Depositing an Al deposition layer on the surface to be welded of the / SiO2 composite material;

[0072] The deposition process of the Al deposition layer is as follows: SiO 2f The / SiO2 composite material is clamped on the workbench of the magnetron sputtering device, and the target and SiO 2f The spacing between the / SiO2 composite materials was 10 cm, and the magnetron sputtering device was evacuated to 5×10 -3 Pa, then introduce 100 sccm of argon at a constant rate, keep the working gas pressure at 0.5 Pa, and set the frequency of the pulse power supply to f r =600Hz, the discharge pulse width is set to t ON = 300μs, select the constant current mode, set the average discharge current to 0.4A, and then gradually increase the voltage applied to the target until the target is completely melted; then perform sputtering deposition for 60min. 2f A 6 μm Al deposition layer is obtained on the surface to be welded of the / SiO2 composite material; the target material is an aluminum target;

[0073] 7. SiO 2f Surface modification of / SiO2 composite materials by aluminothermic reduction

[0074] The SiO2 with Al deposition layer on the surface to be welded 2f The / SiO2 composite material was placed in a vacuum furnace and first heated to 700°C at a heating rate of 10°C / min and kept at this temperature for 2h for reduction modification, and then cooled to 100°C at a cooling rate of 5°C / min;

[0075] 2. Pre-welding treatment of Invar alloy:

[0076] The Invar alloy is cut to a predetermined size, the surface to be welded of the Invar alloy is polished, and then ultrasonically cleaned;

[0077] The ultrasonic cleaning process is as follows: using anhydrous ethanol as a cleaning agent, an ultrasonic cleaning frequency of 100 kHz, and an ultrasonic cleaning time of 10 minutes; using 600-mesh sandpaper to grind the surface of the Invar alloy to be welded;

[0078] 3. Pre-welding treatment of composite intermediate layer:

[0079] Take AgCuTi foil, AgCu foil and Nb foil, cut the AgCuTi foil into 5mm×5mm, cut the AgCu foil into 6mm×6mm, and cut the Nb foil into 6mm×6mm; after cutting, grind, flatten and ultrasonically clean in sequence;

[0080] During the polishing process, 1500-mesh sandpaper is used to polish the AgCuTi foil and the AgCu foil, and 400-mesh sandpaper is used to polish the Nb foil;

[0081] During the flattening process, a flat plate is used to clamp the AgCuTi foil, the AgCu foil and the Nb foil, and a pressure of 8 MPa is applied;

[0082] The ultrasonic cleaning process is as follows: using anhydrous ethanol as a cleaning agent, an ultrasonic cleaning frequency of 100 kHz, an ultrasonic cleaning time of 10 minutes, and repeating the cleaning three times;

[0083] 4. Assembly of test pieces to be welded:

[0084] The SiO obtained in step 1 2f / SiO2 composite material, Invar alloy obtained in step 2, AgCuTi foil, AgCu foil and Nb foil obtained in step 2 are stacked to obtain a welded specimen; the stacking order is SiO 2f / SiO2 composite materials, AgCuTi foil, Nb foil, AgCu foil, Invar alloy, SiO 2f The surface to be welded of the / SiO2 composite material faces the AgCuTi foil, and the surface to be welded of the Invar alloy faces the AgCu foil;

[0085] 5. Vacuum brazing connection: Place the assembled test piece into a vacuum brazing furnace with a vacuum degree of 5×10 -3 Pa, heated to 860 °C at a heating rate of 10 °C / min, kept at that temperature for 20 min, and then cooled to 100 °C at a cooling rate of 5 °C / min.

[0086] Example 1 SiO 2f The shear strength of the brazed joint between the / SiO2 composite material and Invar alloy is 54MPa.

[0087] Embodiment 2:

[0088] In this embodiment, the surface modification of SiO 2f The method for brazing the / SiO2 composite material with Invar alloy is carried out according to the following steps:

[0089] 1. SiO 2f Pre-welding treatment of SiO2 composite materials:

[0090] ①、 SiO 2f / SiO2 composite material is cut into 4mm×4mm×4mm;

[0091] ②, cut SiO 2f / SiO2 composite materials are ultrasonically cleaned;

[0092] The ultrasonic cleaning process in step 1② is as follows: the cleaning agent is anhydrous ethanol, the ultrasonic cleaning frequency is 100kHz, and the ultrasonic cleaning time is 10min;

[0093] ③. After ultrasonic cleaning, SiO 2f / SiO2 composite material is calcined;

[0094] The calcination process is as follows: heating to 700°C at a heating rate of 10°C / min, keeping the temperature for 60 minutes, and cooling to 100°C at a cooling rate of 5°C / min; calcination can remove SiO 2f / SiO2 composite material internal colloid;

[0095] ④. Polishing SiO 2f / SiO2 composite material surface to be welded;

[0096] Step 1④ SiO 2f The surface to be welded of the SiO2 composite material is polished with 1500-grit sandpaper to remove surface impurities and ensure that the surface to be welded is smooth and flat;

[0097] ⑤、The polished SiO 2f / SiO2 composite materials are ultrasonically cleaned;

[0098] Step 1⑤ The ultrasonic cleaning process is: using anhydrous ethanol as the cleaning agent, the ultrasonic cleaning frequency is 100kHz, the ultrasonic cleaning time is 10min, and the cleaning is repeated 3 times;

[0099] ⑥In SiO 2f Depositing an Al deposition layer on the surface to be welded of the / SiO2 composite material;

[0100] The deposition process of the Al deposition layer is as follows: SiO 2f The / SiO2 composite material is clamped on the workbench of the magnetron sputtering device, and the target and SiO 2f The spacing between the / SiO2 composite materials was 10 cm, and the magnetron sputtering device was evacuated to 5×10 -3 Pa, then introduce 100 sccm of argon at a constant rate, keep the working gas pressure at 0.5 Pa, and set the frequency of the pulse power supply to f r =600Hz, the discharge pulse width is set to tON = 300μs, select the constant current mode, set the average discharge current to 0.4A, and then gradually increase the voltage applied to the target until the target is completely melted; then perform sputtering deposition for 60min. 2f A 6 μm Al deposition layer is obtained on the surface to be welded of the / SiO2 composite material; the target material is an aluminum target;

[0101] 7. SiO 2f Surface modification of / SiO2 composite materials by aluminothermic reduction

[0102] The SiO2 with Al deposition layer on the surface to be welded 2f The / SiO2 composite material was placed in a vacuum furnace and first heated to 700°C at a heating rate of 10°C / min and kept at this temperature for 2h for reduction modification, and then cooled to 100°C at a cooling rate of 5°C / min;

[0103] 2. Pre-welding treatment of Invar alloy:

[0104] The Invar alloy is cut to a predetermined size, the surface to be welded of the Invar alloy is polished, and then ultrasonically cleaned;

[0105] The ultrasonic cleaning process is as follows: using anhydrous ethanol as a cleaning agent, an ultrasonic cleaning frequency of 100 kHz, and an ultrasonic cleaning time of 10 minutes; using 600-mesh sandpaper to grind the surface of the Invar alloy to be welded;

[0106] 3. Pre-welding treatment of composite intermediate layer:

[0107] Take AgCuTi foil, AgCu foil and Nb foil, cut the AgCuTi foil into 5mm×5mm, cut the AgCu foil into 6mm×6mm, and cut the Nb foil into 6mm×6mm; after cutting, grind, flatten and ultrasonically clean in sequence;

[0108] During the polishing process, 1500-mesh sandpaper is used to polish the AgCuTi foil and the AgCu foil, and 400-mesh sandpaper is used to polish the Nb foil;

[0109] During the flattening process, a flat plate is used to clamp the AgCuTi foil, the AgCu foil and the Nb foil, and a pressure of 8 MPa is applied;

[0110] The ultrasonic cleaning process is as follows: using anhydrous ethanol as a cleaning agent, an ultrasonic cleaning frequency of 100 kHz, an ultrasonic cleaning time of 10 minutes, and repeating the cleaning three times;

[0111] 4. Assembly of test pieces to be welded:

[0112] The SiO obtained in step 1 2f / SiO2 composite material, Invar alloy obtained in step 2, AgCuTi foil, AgCu foil and Nb foil obtained in step 2 are stacked to obtain a welded specimen; the stacking order is SiO 2f / SiO2 composite materials, AgCuTi foil, Nb foil, AgCu foil, Invar alloy, SiO 2f The surface to be welded of the / SiO2 composite material faces the AgCuTi foil, and the surface to be welded of the Invar alloy faces the AgCu foil;

[0113] 5. Vacuum brazing connection: Place the assembled test piece into a vacuum brazing furnace with a vacuum degree of 5×10 -3 Pa, heated to 860 °C at a heating rate of 10 °C / min, kept at that temperature for 20 min, and then cooled to 100 °C at a cooling rate of 5 °C / min.

[0114] Example 2 SiO 2f The shear strength of the brazed joint between the / SiO2 composite material and Invar alloy is 56MPa.

[0115] from Figure 1 and Figure 2 It can be seen that in Example 1 and Example 2, the SiO 2f / SiO2 composite material surface modification, enhance the solder and SiO 2f The interface reaction between the brazing filler metal and SiO2 composite material forms a dense and continuous reaction layer, which significantly enhances the 2f / SiO2 composite materials.

Claims

1. Aluminothermic reduction surface modification assisted SiO 2f A method for brazing SiO2 composite material and Invar alloy, characterized in that: Aluminothermic reduction surface modification assisted SiO 2f The method for brazing the / SiO2 composite material with Invar alloy is carried out according to the following steps:

1. SiO 2f Pre-welding treatment of SiO2 composite materials: ①、 SiO 2f / SiO2 composite material is cut to a predetermined size; ②, cut SiO 2f / SiO2 composite materials are ultrasonically cleaned; ③. After ultrasonic cleaning, SiO 2f / SiO2 composite material is calcined; The calcination process is as follows: heating to 700°C-800°C at a heating rate of 5-10°C / min, keeping the temperature for 60-120min, and cooling to ≤150°C at a cooling rate of ≤5°C / min; ④. Polishing SiO 2f / SiO2 composite material surface to be welded; ⑤、The polished SiO 2f / SiO2 composite materials are ultrasonically cleaned; ⑥In SiO 2f Depositing an Al deposition layer on the surface to be welded of the / SiO2 composite material; The deposition process of the Al deposition layer is as follows: SiO 2f The / SiO2 composite material is clamped on the workbench of the magnetron sputtering device, and the target and SiO 2f / SiO2 composite material spacing, the magnetron sputtering device was evacuated to ≤5×10 -3 Pa, then introduce 80-150sccm of argon at a constant rate, keep the working gas pressure at 0.1-0.8Pa, and set the frequency of the pulse power supply to f r =500-700Hz, the discharge pulse width is set to t ON = 200-400μs, select the constant current mode, set the average discharge current to 0.3-0.5A, and then gradually increase the voltage applied to the target until the target is completely melted; then sputter and deposit on SiO 2f An Al deposition layer is obtained on the surface to be welded of the / SiO2 composite material; the target material is an aluminum target; 7. SiO 2f / SiO2 composite material surface aluminothermic reduction modification; The SiO2 with Al deposition layer on the surface to be welded 2f The / SiO2 composite material is placed in a vacuum furnace, first heated to 650°C-700°C at a heating rate of 5-10°C / min and kept at this temperature for 1-4h for reduction modification, and then cooled to ≤150°C at a cooling rate of ≤5°C / min; 2. Pre-welding treatment of Invar alloy: The Invar alloy is cut to a predetermined size, the surface to be welded of the Invar alloy is polished, and then ultrasonically cleaned; 3. Pre-welding treatment of composite intermediate layer: Taking AgCuTi foil, AgCu foil and Nb foil, and cutting them into predetermined sizes, and then grinding, leveling and ultrasonic cleaning them in sequence after cutting; 4. Assembly of test pieces to be welded: The SiO obtained in step 1 2f / SiO2 composite material, Invar alloy obtained in step 2, AgCuTi foil, AgCu foil and Nb foil obtained in step 2 are stacked to obtain a welded specimen; the stacking order is SiO 2f / SiO2 composite materials, AgCuTi foil, Nb foil, AgCu foil, Invar alloy, SiO 2f The surface to be welded of the / SiO2 composite material faces the AgCuTi foil, and the surface to be welded of the Invar alloy faces the AgCu foil; 5. Vacuum brazing connection: Place the assembled test piece into a vacuum brazing furnace with a vacuum degree of 5×10 - 3 Pa, heat to 840-900℃ at a heating rate of 5-10℃ / min, keep warm for 10-40min, and then cool to ≤150℃ at a cooling rate of ≤5℃ / min.

2. The aluminum thermal reduction surface modification auxiliary SiO according to claim 1 2f A method for brazing SiO2 composite material and Invar alloy, characterized in that: The ultrasonic cleaning process in step 1② is as follows: the cleaning agent is anhydrous ethanol or acetone, the ultrasonic cleaning frequency is 70-150kHz, and the ultrasonic cleaning time is 5-60min.

3. The aluminum thermal reduction surface modification auxiliary SiO according to claim 1 2f A method for brazing SiO2 composite material and Invar alloy, characterized in that: Step 1④ SiO 2f The surface to be welded of the SiO2 composite material is polished with 1000-3000 mesh sandpaper to remove surface impurities and ensure that the surface to be welded is smooth and flat.

4. The aluminum thermal reduction surface modification auxiliary SiO according to claim 1 2f A method for brazing SiO2 composite material and Invar alloy, characterized in that: Step 1⑤ The ultrasonic cleaning process is: using anhydrous ethanol or acetone as a cleaning agent, the ultrasonic cleaning frequency is 70-150kHz, the ultrasonic cleaning time is 5-60min, and the cleaning is repeated 2-3 times.

5. The aluminum thermal reduction surface modification auxiliary SiO according to claim 1 2f A method for brazing SiO2 composite material and Invar alloy, characterized in that: The ultrasonic cleaning process in step 2 is as follows: using anhydrous ethanol or acetone as a cleaning agent, an ultrasonic cleaning frequency of 70-150 kHz, and an ultrasonic cleaning time of 5-60 min; and using 400-1000 mesh sandpaper to grind the surface to be welded of the Invar alloy.

6. The aluminum thermal reduction surface modification auxiliary SiO according to claim 1 2f A method for brazing SiO2 composite material and Invar alloy, characterized in that: In the polishing process described in step 3, 1000-2000 mesh sandpaper is used to polish the AgCuTi foil and the AgCu foil, and 400-1000 mesh sandpaper is used to polish the Nb foil.

7. The aluminum thermal reduction surface modification auxiliary SiO according to claim 1 2f A method for brazing SiO2 composite material and Invar alloy, characterized in that: Step 3: The AgCuTi foil, AgCu foil and Nb foil are cut to an edge larger than the SiO 2f / SiO2 composite material edge of the surface to be welded is 1-2mm.

8. The aluminum thermal reduction surface modification auxiliary SiO according to claim 1 2f A method for brazing SiO2 composite material and Invar alloy, characterized in that: In the flattening process of step 3, a flat plate is used to clamp the AgCuTi foil, the AgCu foil and the Nb foil, and a pressure of 5-10 MPa is applied.

9. The aluminum thermal reduction surface modification auxiliary SiO according to claim 1 2f A method for brazing SiO2 composite material and Invar alloy, characterized in that: The ultrasonic cleaning process in step 3 is: using anhydrous ethanol or acetone as a cleaning agent, an ultrasonic cleaning frequency of 70-150kHz, an ultrasonic cleaning time of 5-60min, and repeating the cleaning 2-3 times.

10. The aluminum thermal reduction surface modification auxiliary SiO according to claim 1 2f A method for brazing SiO2 composite material and Invar alloy, characterized in that: Step 1⑥ The deposition process of the Al deposition layer is: 2f The / SiO2 composite material is clamped on the workbench of the magnetron sputtering device, and the target and SiO 2f The spacing between the / SiO2 composite materials was 10 cm, and the magnetron sputtering device was evacuated to 5×10 -3 Pa, then introduce 100 sccm of argon at a constant rate, keep the working gas pressure at 0.5 Pa, and set the frequency of the pulse power supply to f r =600Hz, the discharge pulse width is set to t ON = 300μs, select the constant current mode, set the average discharge current to 0.4A, and then gradually increase the voltage applied to the target until the target is completely melted; then perform sputtering deposition for 60min. 2f A 6μm Al deposition layer was obtained on the surface to be welded of the / SiO2 composite material.

Citation Information

Patent Citations

  • Method for diffusing and brazing SiCp / Al composite material by virtue of Al / Cu / Al composite foil

    CN103978277A

  • SiO2-BN composite ceramic and Invar alloy brazing method

    CN108296586A

  • Brazed quartz fiber reinforced composite ceramic and Invar alloy composite solder as well as preparation method and brazing method thereof

    CN108555476A

  • Compound brazing material for brazing quartz short fiber enhanced silicon dioxide composite material and Invar alloys as well as preparation method thereof

    CN108620767A

  • Self-alloying connection method for Cf / C and Cf / SiC composite and stainless steel

    CN109180212A